2010
DOI: 10.1111/j.1442-9071.2010.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic testing in retinoblastoma management at a tertiary referral centre

Abstract: Advances in gene testing have enabled a high rate of mutation detection, particularly when tumour tissue is genotyped. Genetic analysis is integral to the management of retinoblastoma patients allowing enhanced follow-up care, avoidance of unnecessary examinations, family screening, counselling and reproductive planning, with early tumour detection in predisposed individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Children with heritable RB, in addition to experiencing bilateral vision impairment in early childhood, are at increased risk for developing primitive neuroectodermal tumors and second tumors later in life. The genetically predisposed individuals can be screened ophthalmologically and the tumors treated as they arise.Unequivocal identification of mutant gene carriers will also eliminate the need for costly and time-consuming procedures for family members who are not carriers (19,20). On the other hand, the large size of the RB1 gene (180 kb), its high degree of mutational heterogeneity, the high proportion of mutations arise from small (< 10 bp) sequence changes and the presence of mosaicism and the possibility of mutation within non-coding regions make it very difficult to achieve efficient detection of RB1 mutations for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Children with heritable RB, in addition to experiencing bilateral vision impairment in early childhood, are at increased risk for developing primitive neuroectodermal tumors and second tumors later in life. The genetically predisposed individuals can be screened ophthalmologically and the tumors treated as they arise.Unequivocal identification of mutant gene carriers will also eliminate the need for costly and time-consuming procedures for family members who are not carriers (19,20). On the other hand, the large size of the RB1 gene (180 kb), its high degree of mutational heterogeneity, the high proportion of mutations arise from small (< 10 bp) sequence changes and the presence of mosaicism and the possibility of mutation within non-coding regions make it very difficult to achieve efficient detection of RB1 mutations for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for any mutation of the RB1 gene from both tumor and peripheral blood can identify the germline mutation, which may help in proper management planning for both the affected child and sibling [23]. Genetic counseling supports families to understand medical diagnosis, disease prognosis, and risk of transmission of disease to offspring.…”
Section: Leukemic Infiltratementioning
confidence: 99%
“…Studies have shown that approximately 15% of unilateral cases are due to germline mutations, and they can subsequently develop tumors in the unaffected eye 59 . Therefore, early genotyping can provide crucial insights into what type of retinoblastoma the patient has, enabling optimal treatment plans and genetic counseling 60 . Recently, there has been a potentially exciting development of cell-free DNA analysis of aqueous humor samples that can detect mutations in tumor cells with a high accuracy rate.…”
Section: Retinoblastomamentioning
confidence: 99%